Social innovation in the commercialization of organic and agroecological products of family farming in Brazil’s Federal District - Sabourin, Eric Pierre; Thomas, Segolene; Egret, Lea; Avila, Mario (Sustainability in Debate, 2014)
The Federal District and particularly the city of Brasilia constitute a booming market for organic and agro-ecological products. This paper develops a characterization of the modes of family farmer’s organization for marketing of organic and agroecological products in the Federal District of Brasilia. The methodology has associated an analysis of documents and statistics and interviews of the various actors of the two main chains of products in the Federal District: producers of the agro-ecological fairs, farmer’s organizations, supermarkets, extension agents and technicians of public agencies. Family farmers have progressively invested the short food chains with direct sales and agro-ecological fairs, through specific and innovative modalities of coordination and organization. The main results show a combination between formal and informal status and institutions and the mobilization of renewed forms of reciprocity, mutual help and collective learning.